Análise dos dados do SISAGUA e validação de método para determinação de agrotóxicos em água potável a fim de atender as legislações brasileiras - Babinski, Paola Jennifer (2024)
Water is the foundation of life, playing an essential role in different contexts, which makes it crucial to ensure its availability in adequate quantity and quality. To maintain water potability standards is a challenge because contemporary agriculture use pesticides to meet the global demand for food. However, this practice brings substantial risks to the environment and human health. In Brazil, drinking water potability is regulated by Ordinance GM/MS Nº 888/2021, which establishes the maximum allowable concentrations (MAC) for pesticides and their metabolites. Monitoring of pesticide residues in supply systems is carried out by the National Water Quality Surveillance Program for Human Consumption (VIGIAGUA) and the data is accessible at the Water Quality Surveillance Information System for Human Consumption (SISAGUA). Therefore, the present study aimed to: 1) Evaluate the SISAGUA database related to pesticide residues in water samples from the states of Rio Grande do Sul and São Paulo from 2014 to 2022; 2) To develop and to validate an integrated SPE-LC-MS/MS method for pesticides determination in drinking water. The evaluation of the SISAGUA database revealed that 20 out of the 27 pesticides monitored in the Brazilian water supply systems have results above the MAC, including pesticides banned for agricultural use in Brazil. Aldrin and dieldrin was the most frequently detected pesticide and were found in 40 samples, covering 52% of municipalities, in concentrations between 0.04 and 15 μg L-1. For the extraction of pesticides, the use of C18 and Oasis® HLB cartridges were evaluated, followed by elution by dichloromethane and methanol or ethyl acetate. The best results were achieved using the Oasis® HLB sorbent. The validation study showed that the calculated r2 values were ≥ 0.99 for all analytes, when the analytical curves were prepared in matrix extract, demonstrating satisfactory linearity. The spiking experiments were performed by different analysts, with a 21 days-interval demonstrated accuracy and precision at the spike concentrations of 0.2; 0.5; 1 and 3 μg L-1 (n=7), presenting average recovery percentages of 79 to 135% and relative standard deviations of repeatability (RSDr) of up to 20%. Within-laboratory reproducibility (RSDwR) showed a repeatability < 20% for all analytes at the highest spike concentration. The multiresidue method was validated for the determination of 29 pesticides. The limit of quantification was 0.2 μg L-1 and 0.5 μg L-1 for 10.3% and 89.7% of those studied pesticides, respectively. The developed method is considered suitable for determining pesticides in drinking water and can be adopted as an alternative by laboratories that receive samples collected by VIGIAGUA teams.